Pelatihan Pengembangan Konten Pemasaran Melalui Media Sosial Untuk Membantu Perkembangan UMKM Di Kelurahan Keputih - Rahma Febriana; Riko Setya Wijaya; M. Taufiq (jurnal ABDIMAS Indonesia, 2023)
MSMEs play an important role in the Indonesian economy. Therefore, the development and progress of MSMEs is very important. One of the efforts to increase the development of MSMEs is through promotional strategies by creating attractive and innovative marketing content. In addition, MSME players must also be able to utilize social media as an effective and efficient promotion and sales media. Both of these are good strategies, especially in the current digitalization era. However, after conducting a field survey, it was found that MSME players in the Keputih village area did not understand how to create content and utilize social media properly. Therefore, the group 74 KKN-T MBKM UPN "Veteran" East Java conducted training with the theme "Content Development and Social Media Management" as a solution to this problem. This research was conducted using survey and interview methods with a qualitative approach. This training was held on May 20, 2023 at the Keputih Harmony Tourism Market with the target of MSME players in the Keputih Harmony Tourism Market (PWHK) and MSMEs in the Keputih area but outside PWHK. This training produces output in the form of material and hones soft skills skills regarding the creation of interesting and innovative marketing content and how to manage social media to increase sales of MSME products in the Keputih Village area.